2022
DOI: 10.1177/20420986221116465
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes toward deprescribing and their experiences communicating with clinicians and pharmacists

Abstract: Purpose: Developing effective deprescribing interventions relies on understanding attitudes, beliefs, and communication challenges of those involved in the deprescribing decision-making process, including the patient, the primary care clinician, and the pharmacist. The objective of this study was to assess patients’ beliefs and attitudes and identify facilitators of and barriers to deprescribing. Methods: As part of a larger study, we recruited patients ⩾18 years of age taking ⩾3 chronic medications. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…To the best of our knowledge, this is the first time that sex has been reported as a predictor of the willingness to have medications deprescribed. Previous studies found that the association between participants' sex and the willingness to have medications deprescribed was not significant 20–23,26,27,30,33,35,37–39,44 . Our result may be partly explained by the noteworthy differences between women and men in their medication adherence, with women being less likely to follow preventive guidance and less adherent to medicines 60,61 .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first time that sex has been reported as a predictor of the willingness to have medications deprescribed. Previous studies found that the association between participants' sex and the willingness to have medications deprescribed was not significant 20–23,26,27,30,33,35,37–39,44 . Our result may be partly explained by the noteworthy differences between women and men in their medication adherence, with women being less likely to follow preventive guidance and less adherent to medicines 60,61 .…”
Section: Discussioncontrasting
confidence: 52%
“…For example, age and willingness to have medications deprescribed were found to be positively associated in four studies, 20,21,29,30 negatively associated in another four studies, 18,19,22,31 and non‐significant in 15 other studies 23–27,32–41 . Among the 21 studies that examined the association between patient willingness to have a medication deprescribed and the number of medications, three found a positive association, 20,22,23 one a negative association, 34 and 17 found no significant association 21,24–27,29,30,32,33,36,37,39,40,42–45 . These unclear findings support the need for more research on what factors are associated with the patients' willingness to have their medications deprescribed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may lead to not preferring any other pharmacist services than the short face-to-face consultation when collecting the medication [ 25 ]. In a study conducted in the USA, one in five patients indicated never communicating with the pharmacist, but when such communication was perceived effective it was associated with a higher willingness to accept deprescribing [ 14 ]. A study in Singapore found that only half of the patients felt comfortable with pharmacists being involved in the deprescribing process in primary care [ 26 ], while more than 70% of patients in Croatia had a positive opinion on pharmacists’ involvement in deprescribing [ 12 ]..…”
Section: Discussionmentioning
confidence: 99%
“…One study in Croatia found that patients were comfortable with pharmacists’ involvement in deprescribing process, and that they had a positive opinion on their pharmacists’ competencies regarding deprescribing [ 12 ]. In addition, patients who perceived more effective communication with their general practitioner or pharmacist were more willing to accept deprescribing [ 14 ]. At country level, it was found that patients in low-middle-income countries (LMIC) may be less willing to stop medication compared to high-income countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%